AN ANALYSIS OF SLANG IN GEEK CHARMING MOVIE - Lumendang, Ien Meise; Samola, Nurmin; Kumayas, Tirza (Journal of English Culture, Language, Literature and Education, 2020)
Sociolinguistics has a lot of aspects that can be researched One of the aspects is slang Slang is vocabulary that is used between people who belong to the same social group and who know each other well Slang is very informal language This research mainly discussed about slang in Geek Charming Movie The purpose of this study is to identify the slangs and to describe the types of slang used in Geek Charming Movie This study is limited to the main characters in the movie they are Dylan Schoenfield and Josh Rosen The writer used descriptive qualitative method by using Bodgan and Bilden 1992 theory which consists of four steps: unitization categorization explanation and interpretation After analizing the data it is found out that there are three types of slang used by Dylan Schoen field and Josh Rosen in Geek Charming Movie The types of slang are public house slang society slang slangin public school and university Those are types of slang according to Eric Partridge 1950 It is important to study slang because the result of this research can be used for further research and help readers to get more knowledge about slang < p>